The pre-hospital treatment of paediatric injuries (a preliminary report) - Kuziemska, Anna; Skotnicka-Klonowicz, Grażyna (Polish Journal of Public Health, 2009)
Introduction. Injuries to children are the most important problems in paediatric emergency medicine. Treatment of paediatric injuries should start immediately after the accident occurs.Objective. Analysis of pre-hospital treatment of children with injuries.Material and methods. The study comprised 68 children from among 400 children who were admitted with injuries to the Emergency Department. This group of patients received first aid from health care professionals during the period from 23.02.2009 to 23.03.2009. We analyzed sex, age, kind of trauma, location and mechanism of injury, circumstances of accident and the quality of first aid.Results. During the period of this study, injuries in the group comprised twice as many boys as girls (62.1 9% boys 27.9% girls). Children over 10 years (62.1%) more often had injuries than other children in the group. Head injuries and injuries of upper limbs were noticed in 24 children (35.9%), 21 children suffered from lower limb injuries and 5 children (7.4%) had burns. Two children had abdomen injuries and 1 child suffered from chest and 1 from spine injuries. Thirty five children (51.5%) were transported by ambulance to emergency hospital departments; in this group 40% were transported by “basic ambulance” and 60% were transported by “specialist ambulance”. Twenty one children (30.8%) were treated by GP doctors and 12 (17.6%) by school nurses. In the majority of cases, the pre-hospital treatment offered by health care workers was correct. However, in 19.1% of children pre-hospital treatment was performed incorrectly. Nine children did not receive painkillers, in 2 cases wounds were not dressed correctly and 2 children were not provided with proper immobilization of fractures.Conclusions. Preliminary results of the analysis of treatments offered by health care professionals to children after injury cause concern and confirm the need for continued research to improve child-care after injury.